Preparation method of granulated material for friction material and its application in copper-free NAO type brake pads for high-end agricultural machinery and equipment
By using nano-titanium dioxide-straw fiber multi-scale reinforcement and copper powder replacement materials in brake pads for high-end agricultural machinery equipment, the problems of weak bonding performance and serious dust pollution are solved, and the fluidity of the brake pads are achieved. The improvement of mechanical properties and wear resistance reduces environmental pollution and production costs.
Patent Information
- Application Number
- CN202111180222.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2021-10-11
- Publication Date
- 2025-02-18
- Estimated Expiration
- 2041-10-11
AI Technical Summary
The brake pads for existing high-end agricultural machinery equipment have weak bonding performance between straw fiber and resin matrix, lack of obvious reinforcement effect of single fiber, poor fluidity of brake pad raw materials, severe dust pollution, poor physical and mechanical properties, unstable friction factor, and wear resistance. Poor properties and copper dust pollution.
Using nano-titanium dioxide-straw fiber multi-scale reinforcement and copper powder replacement materials, the fluidity, bonding performance and resistance of the brake pads are improved through the preparation of granulated substances and the process flow of copper-free NAO-type brake pads for high-end agricultural machinery equipment. Abrasiveness, reducing dust pollution and noise pollution.
It improves the flowability and mechanical properties of the brake pad, reduces dust pollution and noise pollution, stabilizes the friction factor, improves the wear resistance and reliability of the brake pad, and reduces production costs and environmental pollution.
Abstract
Description
Technical Field
[0001] The present invention relates to a brake pad, in particular to a granulated material used for friction material and a copper-free NAO type brake pad for high-end agricultural machinery and equipment, belonging to the technical field of agricultural machinery and equipment accessories. Background Art
[0002] Agricultural machinery is an important carrier of modern agricultural science and technology, and agricultural mechanization is an important symbol of agricultural modernization. To vigorously promote agricultural modernization, we must focus on strengthening material equipment and technical support. Moving towards the goal of full mechanization of agriculture has put forward the requirement of accelerating the development of high-end agricultural machinery and equipment. At present, the high-end agricultural machinery and equipment market is still monopolized by imported products, and the supply of independent high-end agricultural machinery and equipment is insufficient. As the most critical safety parts in the braking system of agricultural machinery and equipment, the performance of brake pads is directly related to the safety, stability and reliability of the operation of agricultural machinery and equipment systems, especially the accuracy of the operation of high-end intelligent agricultural machinery and equipment. With the acceleration of land transfer in my country, agricultural machinery and equipment are developing towards large-scale and high-efficiency, and the intelligence, automation and refinement capabilities of high-end agricultural machinery and equipment products are constantly improving, which also puts forward stringent requirements on the performance of brake pads for high-end agricultural machinery and equipment. This requires researchers engaged in brake pads for agricultural machinery and equipment to continuously explore new methods, solve new problems, and develop brake friction materials with good comprehensive performance and meet the characteristics and needs of high-end agricultural machinery and equipment.
[0003] At present, there are relevant patent reports at home and abroad for high-performance, automotive brake friction materials that meet different types of requirements, such as:
[0004] The Chinese patent publication number is 113214597A, the publication date is 2021.08.06, and the invention name is "Basalt fiber-based high-performance environmentally friendly friction material and preparation method". The invention discloses a friction material for automobiles;
[0005] The Chinese patent publication number is 112940447A, the publication date is 2021.06.11, and the invention name is "A friction material, brake pad and preparation method for electric vehicles". The invention discloses a brake pad for electric vehicles;
[0006] The Chinese patent publication number is CN110778629B, the publication date is 2021.06.04, and the invention name is "A brake material containing halides and its preparation method and application". The invention discloses an automobile brake pad or a rail vehicle brake pad;
[0007] The Chinese patent publication number is 112855814A, the publication date is 2021.05.28, and the invention name is "A low-noise, rust-proof and adhesion-proof drum brake pad for new energy vehicles and its preparation method", which discloses a drum brake pad for new energy vehicles;
[0008] The Chinese patent publication number is 112855812A, the publication date is 2021.05.28, and the invention name is "A friction material for passenger cars with a high deceleration of 0.8G at a high speed of 200 kilometers and a preparation method thereof". The invention discloses a drum brake pad for passenger cars;
[0009] The Chinese patent announcement number is CN109555802B, the announcement date is 2020.08.18, and the invention name is "A friction material, an organic carbon ceramic brake pad for a wear-resistant coating brake disc prepared therefrom, and a preparation method and application thereof". The invention discloses a friction material for automobiles and new energy vehicles;
[0010] The Chinese patent announcement number is CN106928649B, the announcement date is 2019.07.05, and the invention name is "Ceramic particle composite resin-based heat-fading resistant friction material and preparation method thereof", which discloses a friction material for automobiles;
[0011] The Chinese patent publication number is CN107061571B, the publication date is 2018.11.02, and the invention name is "A rear disc brake material for a truck and its preparation method", which discloses a friction material for a heavy-duty truck;
[0012] However, there are relatively few technologies related to brake pads for high-end agricultural machinery and equipment. As agricultural machinery and equipment develop towards large-scale and high-efficiency, the high-end agricultural machinery and equipment brake system industry has higher and higher requirements for the performance of high-performance brake pads. This requires that the brake pads for high-end agricultural machinery and equipment should be designed based on the characteristics and needs of high-end agricultural machinery and equipment. The formula, internal structure, preparation process and raw material processing of the brake pads should be coordinated to develop brake pads for high-end agricultural machinery and equipment. Summary of the invention
[0013] In view of the problems existing in the prior art, such as weak bonding performance between straw fiber and resin matrix, unclear reinforcement effect of single fiber, poor fluidity of brake pad raw materials, heavy dust pollution in the production process of brake pads, poor physical and mechanical properties of brake pads, serious abrasions on the pairs of brake pads, unstable friction coefficient and poor wear resistance of brake pads, brake dust and noise pollution, large brake vibration, copper dust pollution and waste of straw waste, a method for preparing granulated materials for friction materials and the application of the granulated materials in copper-free NAO type brake pads for high-end agricultural machinery and equipment are proposed.
[0014] The present invention achieves the above technical objectives through the following technical means.
[0015] A copper-free NAO type brake pad for high-end agricultural machinery and equipment, the contents of each component by mass fraction are: 80-95% of granulated material for friction material, 0-10% of nitrile rubber modified phenolic resin and 2-15% of non-straw fiber; wherein the non-straw fiber includes one of rock wool fiber, sepiolite fiber or composite mineral fiber.
[0016] Furthermore, the composition of the granulated material used for the friction material is as follows, by mass fraction, the contents of each component are: 5-20% of nano-titanium dioxide-straw fiber multi-scale reinforcement, 1-5% of rubber powder, 5-20% of nitrile rubber modified phenolic resin, 5-21% of barite, 2-10% of shale, 5-24% of alumina, 1-3% of vermiculite powder, 1-5% of tire powder, 1-5% of purple sand, 1-5% of friction powder, 3-15% of potassium titanate platelets and 2-15% of copper powder substitute material.
[0017] Furthermore, the nano-titanium dioxide-straw fiber multi-scale reinforcement is composed of 20-70% by mass of corn straw fiber and 30-80% by mass of rice straw fiber.
[0018] Furthermore, the copper powder substitute material is composed of 20-40% by mass of stainless steel grinding chips and 60-80% by mass of natural graphite.
[0019] Furthermore, the preparation method of the nano-titanium dioxide-straw fiber multi-scale reinforcement comprises the following steps:
[0020] Step 1: crushing the collected straw skin in a crusher, and then screening the crushed straw fibers;
[0021] Step 2: soaking the straw fiber obtained in step 1 in a grafting treatment device containing a suspension formed by nano-titanium dioxide and silane solution to obtain nano-titanium dioxide-straw fiber;
[0022] Step 3: Put the nano-titanium dioxide-straw fiber obtained in step 2 into an ultrasonic cleaning machine for cleaning, and then dry it in a drying box to finally obtain a nano-titanium dioxide-straw fiber multi-scale reinforcement.
[0023] Furthermore, in step 1, the crushing time t1 of the straw skin is: 3min≤t1≤6min; the straw fiber length L1 is: 1mm≤L1≤3mm, and the fiber diameter D1 is: 0.01mm≤D1≤0.5mm;
[0024] In step 2, the silane solution is composed of anhydrous ethanol, a silane coupling agent and distilled water, the mass ratio of each component is: 35-75:6-15:10-50, the particle size of nano titanium dioxide D2 is: 2nm≤D2≤100nm, the mass fraction w1 of nano titanium dioxide in the suspension is: 0.5%≤w1≤25%, and the immersion time t2 of the straw fiber in the suspension is: 10min≤t2≤50min;
[0025] In step three, the ultrasonic cleaning time t3 is: 2min≤t3≤10min; the ultrasonic cleaning temperature is room temperature; the ultrasonic cleaning medium is distilled water; the drying temperature T1 is: 90°C≤T1≤112°C, and the drying time t4 is: 60min≤t4≤180min.
[0026] A method for preparing a copper-free NAO type brake pad comprises the following steps:
[0027] Including the preparation of granules for friction materials;
[0028] Mixing during the preparation of brake pads;
[0029] Mold filling - hot pressing and heat treatment - surface ablation - post-processing and molding.
[0030] Further, the preparation of the granulated material for the friction material includes:
[0031] S1: Rubber powder, nitrile rubber modified phenolic resin, barite, shale, alumina, vermiculite powder, tire powder, purple sand, friction powder, potassium titanate platelets and copper powder substitute material are placed in a three-dimensional motion mixer and fully mixed. The mixing time t5 is: 3min≤t5≤8min;
[0032] S2: putting the mixed raw materials obtained in step S1 and the nano-titanium dioxide-straw fiber multi-scale reinforcement into a paddle mixer and mixing them thoroughly, and the mixing time t6 is: 1min≤t6≤3min;
[0033] S3: putting the mixed raw materials obtained in step S2 into a granulator for granulation treatment, spraying a bridging liquid into the granulation drum, adjusting the rotation speeds of the granulation drum and the rotary cutter and the spraying amount of the bridging liquid, and obtaining granules after sufficient granulation; the rotation speed r1 of the granulation drum is: 20r / min≤r1≤350r / min; the rotation speed r2 of the rotary cutter is: 70r / min≤r1≤90r / min, and the bridging liquid is one of distilled water, anhydrous ethanol and a corn starch paste solution with a mass fraction of 3wt%;
[0034] S4: The granules obtained in step S3 are placed in a drying box for drying to obtain the final granules for friction material. The drying temperature T2 is: 100°C ≤ T2 ≤ 130°C, the drying time t7 is: 100min ≤ t7 ≤ 240min, and the obtained granules are cell-like in shape, with a diameter D3 of: 1mm ≤ D3 ≤ 8mm.
[0035] Furthermore, the mixing process in the brake pad preparation process includes the following steps:
[0036] S1: putting the nitrile rubber modified phenolic resin and the non-straw fiber into a paddle mixer and mixing them thoroughly, and the mixing time t8 is: 5min≤t8≤20min;
[0037] S2: The mixture obtained in step S1 and the granulated material for friction material are placed in a three-dimensional motion mixer for thorough mixing. The mixing time t9 is: 5min≤t9≤10min, to obtain the final mixed material for preparing the brake pad.
[0038] Furthermore, mold filling-hot pressing heat treatment-surface ablation-post-processing molding includes the following steps:
[0039] S1: placing the mixed material for preparing the brake pad into a special mold for preparing the brake pad, then performing a hot pressing treatment, and finally performing a heat treatment, and cooling to room temperature;
[0040] S2: ablating the surface of the brake pad sample obtained in step S1 in a through-type ablation machine and cooling to room temperature;
[0041] S3: The ablated surface of the brake pad sample obtained in step S2 is polished, then ground and cut, then spray-painted and baked, and finally a warning device or a fixing device is installed to finally obtain a copper-free NAO type brake pad.
[0042] The beneficial effects of the present invention are:
[0043] 1. The present invention is used for the preparation of friction material granules, which can enhance the fluidity of brake pad raw materials, reduce dust pollution and fiber segregation during the preparation of brake pads, reduce the density of brake pads, stabilize the friction factor, improve the wear resistance and reliability of brake pads, and reduce the amount of brake dust;
[0044] 2. By adopting nano-titanium dioxide-straw fiber multi-scale reinforcement, the interface bonding performance between the straw fiber and the resin matrix can be improved, the friction stress can be effectively transmitted, the mechanical properties and wear resistance of the brake pad can be improved, and the vibration of the brake pad during use can be reduced.
[0045] 3. The nano-titanium dioxide-straw fiber multi-scale reinforcement in the present invention is composed of 20-70% corn straw fiber and 30-80% rice straw fiber by mass fraction. The above components can improve the utilization rate of agricultural waste straw, enhance the environmental performance of the brake pad, reduce resource waste, and reduce the production cost of the brake pad;
[0046] 4. The use of copper powder as an alternative material can prevent the emission of copper particles during braking, reduce environmental pollution and noise pollution, and extend the service life of the brake pads. DETAILED DESCRIPTION
[0047] In the present invention, unless otherwise clearly specified and limited, the terms "installed", "connected", "connected", "fixed" and the like should be understood in a broad sense, for example, it can be a fixed connection, a detachable connection, or an integral connection; it can be a mechanical connection or an electrical connection; it can be a direct connection, or it can be an indirect connection through an intermediate medium, or it can be the internal communication of two components. For ordinary technicians in this field, the specific meanings of the above terms in the present invention can be understood according to specific circumstances.
[0048] A method for preparing a granulated material for friction material and its application in a copper-free NAO type brake pad for high-end agricultural machinery and equipment, wherein the copper-free NAO type brake pad for high-end agricultural machinery and equipment contains a granulated material for friction material, a nitrile rubber-modified phenolic resin and non-straw fiber, and its preparation process mainly includes mold filling-hot pressing heat treatment-surface ablation-post-processing molding, etc. By adopting the above process steps and the above raw material components, the composition and preparation process of the brake pad are controlled during the preparation process, and the comprehensive performance of the brake pad can be directly controlled and adjusted to meet the performance requirements of the brake pad for high-end agricultural machinery and equipment under different working conditions.
[0049] Example 1
[0050] The copper-free NAO brake pads for high-end agricultural machinery and equipment contain the following components by mass fraction: 80% granulated material for friction material, 5% nitrile rubber modified phenolic resin, and 15% non-straw fiber; the non-straw fiber is rock wool fiber.
[0051] The granulated material used for friction material contains the following components by mass fraction: 20% nano-titanium dioxide-straw fiber multi-scale reinforcement, 5% rubber powder, 20% nitrile rubber modified phenolic resin, 21% barite, 10% shale, 5% alumina, 3% vermiculite powder, 5% tire powder, 1% purple sand, 5% friction powder, 3% potassium titanate platelets, and 2% copper powder substitute. The nano-titanium dioxide-straw fiber multi-scale reinforcement is composed of 20% corn straw fiber and 80% rice straw fiber by mass fraction; the copper powder substitute is composed of 40% stainless steel grinding dust and 60% natural graphite by mass fraction.
[0052] The preparation method of nano titanium dioxide-straw fiber multi-scale reinforcement comprises the following specific steps:
[0053] 3.1 The collected straw skin is crushed in a crusher, the crushing time t1 is: 3min, and then the crushed straw fiber is screened, the straw fiber length L1 is: 1mm, and the fiber diameter D1 is: 0.01mm;
[0054] 3.2 Soak the straw fiber obtained in step 3.1 in a grafting treatment device containing a suspension formed by nano-titanium dioxide and silane solution to obtain nano-titanium dioxide-straw fiber. The silane solution is composed of anhydrous ethanol, a silane coupling agent and distilled water, the mass ratio of each component is: 35:15:50, the particle size of nano-titanium dioxide is D2: 2nm, the mass fraction of nano-titanium dioxide in the suspension is w1: 0.5%, and the immersion time t2 of the straw fiber in the suspension is: 10min;
[0055] 3.3 The nano-titanium dioxide-straw fiber obtained in step 3.2 is placed in an ultrasonic cleaning machine for cleaning, the cleaning time t3 is 2 minutes, the ultrasonic cleaning temperature is room temperature, and the ultrasonic cleaning medium is distilled water. Then it is dried in a drying box, the drying temperature T1 is 90°C, and the drying time t4 is 60 minutes, and finally a nano-titanium dioxide-straw fiber multi-scale reinforcement is obtained;
[0056] The preparation method of copper-free NAO brake pads for high-end agricultural machinery and equipment, the specific steps are as follows:
[0057] 4.1 The granulated material for friction material described in the preparation of the copper-free NAO type brake pad for high-end agricultural machinery equipment comprises the following steps:
[0058] 4.1.1 Rubber powder, nitrile rubber modified phenolic resin, barite, shale, alumina, vermiculite powder, tire powder, purple sand, friction powder, potassium titanate platelets and copper powder substitute materials are placed in a three-dimensional motion mixer and mixed thoroughly. The mixing time t5 is: 8min;
[0059] 4.1.2 The mixed raw materials obtained in step 3.1.1 and the nano-titanium dioxide-straw fiber multi-scale reinforcement are placed in a paddle mixer and mixed thoroughly. The mixing time t6 is: 3 min;
[0060] 4.1.3 Put the mixed raw materials obtained in step 4.1.2 into a granulator for granulation treatment, and continuously spray the bridging liquid into the granulation drum, and continuously adjust the rotation speeds of the granulation drum and the rotary knife and the spraying amount of the bridging liquid. After sufficient granulation, a granulated material is obtained. The rotation speed r1 of the granulation drum is 200 r / min; the rotation speed r2 of the rotary knife is 90 r / min, and the bridging liquid is anhydrous ethanol;
[0061] 4.1.4 The granules obtained in step 4.1.3 are placed in a drying oven for drying to obtain the final granules. The drying temperature T2 is 130°C and the drying time t7 is 200 min. The granules obtained are cell-like in shape and have a diameter D3 of 5 mm.
[0062] 4.2 The mixing process in the preparation of brake pads includes the following steps:
[0063] 4.2.1 The nitrile rubber modified phenolic resin and the non-straw fiber are placed in a paddle mixer and mixed thoroughly. The mixing time t8 is 15 min.
[0064] 4.2.2 The mixture obtained in step 4.2.1 and the granulated material obtained in step 4.1.4 are placed in a three-dimensional motion mixer and mixed thoroughly. The mixing time t9 is 10 min to obtain the final mixed material for preparing the brake pad.
[0065] 4.3 Mold filling - hot pressing heat treatment - surface ablation - post-processing molding, including the following steps:
[0066] 4.3.1 Place the mixture obtained in step 4.2.2 into a special mold for brake pads for agricultural machinery and equipment, then perform hot pressing, and finally perform heat treatment and cool to room temperature;
[0067] 4.3.2 ablating the surface of the brake pad sample obtained in step 4.3.1 in a through-type ablation machine and cooling to room temperature;
[0068] 4.3.3 The ablated surface of the brake pad sample obtained in step 4.3.2 is surface polished, then ground and cut, then sprayed and baked, and finally a warning device or a retainer is installed to finally obtain a copper-free NAO type brake pad for high-end agricultural machinery equipment.
[0069] The friction coefficient of the brake pad produced by the process of the above embodiment is in the range of 0.341 to 0.456, and the wear rate is 0.15× 10 -7 cm 3 / Nm~0.30×10 -7 cm 3 / Nm, brake noise and brake dust are significantly reduced.
[0070] Example 2
[0071] The copper-free NAO brake pads for high-end agricultural machinery and equipment contain the following components by mass fraction: 95% granulated material for friction material and 5% non-straw fiber; the non-straw fiber is sepiolite fiber.
[0072] The granulated material used for friction material contains the following components by mass fraction: 18% nano-titanium dioxide-straw fiber multi-scale reinforcement, 1% rubber powder, 12% nitrile rubber modified phenolic resin, 5% barite, 2% shale, 24% alumina, 1% vermiculite powder, 1% tire powder, 5% purple sand, 1% friction powder, 15% potassium titanate platelets, and 15% copper powder substitute. The nano-titanium dioxide-straw fiber multi-scale reinforcement is composed of 70% corn straw fiber and 30% rice straw fiber by mass fraction; the copper powder substitute is composed of 20% stainless steel grinding dust and 80% natural graphite by mass fraction.
[0073] The preparation method of nano titanium dioxide-straw fiber multi-scale reinforcement comprises the following specific steps:
[0074] 3.1 The collected straw skin is crushed in a crusher, the crushing time t1 is: 6min, and then the crushed straw fiber is screened, the straw fiber length L1 is: 3mm, and the fiber diameter D1 is: 0.5mm.
[0075] 3.2 The straw fiber obtained in step 3.1 is immersed in a grafting treatment device containing a suspension formed by nano-titanium dioxide and silane solution to obtain nano-titanium dioxide-straw fiber. The silane solution is composed of anhydrous ethanol, a silane coupling agent and distilled water, the mass ratio of each component is: 75:6:19, the particle size of nano-titanium dioxide is D2: 100nm, the mass fraction w1 of nano-titanium dioxide in the suspension is: 25%, and the immersion time t2 of the straw fiber in the suspension is: 50min.
[0076] 3.3 The nano-titanium dioxide-straw fiber obtained in step 3.2 is placed in an ultrasonic cleaning machine for cleaning, the cleaning time t3 is: 10 minutes, the ultrasonic cleaning temperature is room temperature, and the ultrasonic cleaning medium is distilled water. Then it is dried in a drying box, the drying temperature T1 is: 100°C, and the drying time t4 is: 180 minutes, and finally a nano-titanium dioxide-straw fiber multi-scale reinforcement is obtained.
[0077] The preparation method of copper-free NAO brake pads for high-end agricultural machinery and equipment, the specific steps are as follows:
[0078] 4.1 The granulated material for friction material described in the preparation of the copper-free NAO type brake pad for high-end agricultural machinery equipment comprises the following steps:
[0079] 4.1.1 Rubber powder, nitrile rubber modified phenolic resin, barite, shale, alumina, vermiculite powder, tire powder, purple sand, friction powder, potassium titanate platelets and copper powder substitute materials are placed in a three-dimensional motion mixer and fully mixed. The mixing time t5 is: 5min;
[0080] 4.1.2 The mixed raw materials obtained in step 3.1.1 and the nano-titanium dioxide-straw fiber multi-scale reinforcement are placed in a paddle mixer and mixed thoroughly. The mixing time t6 is: 2 min;
[0081] 4.1.3 Put the mixed raw materials obtained in step 4.1.2 into a granulator for granulation treatment, and continuously spray the bridging liquid into the granulation drum, and continuously adjust the rotation speeds of the granulation drum and the rotary knife and the spraying amount of the bridging liquid. After sufficient granulation, a granulated material is obtained. The rotation speed r1 of the granulation drum is: 350r / min; the rotation speed r2 of the rotary knife is: 80r / min, and the bridging liquid is distilled water;
[0082] 4.1.4 The granules obtained in step 4.1.3 are placed in a drying oven for drying to obtain the final granules. The drying temperature T2 is 110°C and the drying time t7 is 240 min. The granules obtained are cell-like in shape and have a diameter D3 of 8 mm.
[0083] 4.2 The mixing process in the preparation of brake pads includes the following steps:
[0084] 4.2.1 The nitrile rubber modified phenolic resin and the non-straw fiber are placed in a paddle mixer and mixed thoroughly. The mixing time t8 is 5 min.
[0085] 4.2.2 The mixture obtained in step 4.2.1 and the granulated material obtained in step 4.1.4 are placed in a three-dimensional motion mixer and mixed thoroughly. The mixing time t9 is 8 min to obtain the final mixed material for preparing the brake pad.
[0086] 4.3 Mold filling - hot pressing heat treatment - surface ablation - post-processing molding, including the following steps:
[0087] 4.3.1 Place the mixture obtained in step 4.2.2 into a special mold for brake pads for agricultural machinery and equipment, then perform hot pressing, and finally perform heat treatment and cool to room temperature;
[0088] 4.3.2 ablating the surface of the brake pad sample obtained in step 4.3.1 in a through-type ablation machine and cooling to room temperature;
[0089] 4.3.3 The ablated surface of the brake pad sample obtained in step 4.3.2 is surface polished, then ground and cut, then sprayed and baked, and finally a warning device or a retainer is installed to finally obtain a copper-free NAO type brake pad for high-end agricultural machinery equipment.
[0090] The friction coefficient of the brake pad produced by the process of the above embodiment is in the range of 0.331 to 0.446, and the wear rate is 0.14× 10 -7 cm 3 / Nm~0.32×10 -7 cm 3 / Nm, brake noise and brake dust are significantly reduced.
[0091] Example 3
[0092] The copper-free NAO brake pads for high-end agricultural machinery and equipment contain the following components by mass fraction: 88% granulated material for friction material, 10% nitrile rubber modified phenolic resin, and 2% non-straw fiber; the non-straw fiber is a composite mineral fiber.
[0093] The granulated material used for friction material contains the following components by mass fraction: 5% nano-titanium dioxide-straw fiber multi-scale reinforcement, 4% rubber powder, 5% nitrile rubber modified phenolic resin, 19% barite, 8% shale, 22% alumina, 2% vermiculite powder, 3% tire powder, 3% purple sand, 3% friction powder, 12% potassium titanate platelets, and 14% copper powder substitute material. The nano-titanium dioxide-straw fiber multi-scale reinforcement is composed of 50% corn straw fiber and 50% rice straw fiber by mass fraction; the copper powder substitute material is composed of 30% stainless steel grinding dust and 70% natural graphite by mass fraction.
[0094] The preparation method of nano titanium dioxide-straw fiber multi-scale reinforcement comprises the following specific steps:
[0095] 3.1 The collected straw skin is crushed in a crusher, the crushing time t1 is: 5min, and then the crushed straw fiber is screened, the straw fiber length L1 is: 2mm, and the fiber diameter D1 is: 0.05mm.
[0096] 3.2 Soak the straw fiber obtained in step 3.1 in a grafting treatment device containing a suspension formed by nano-titanium dioxide and silane solution to obtain nano-titanium dioxide-straw fiber. The silane solution is composed of anhydrous ethanol, a silane coupling agent and distilled water, the mass ratio of each component is: 78:12:10, the particle size of nano-titanium dioxide is D2: 50nm, the mass fraction of nano-titanium dioxide in the suspension is w1: 15%, and the straw fiber is immersed in the suspension for t2: 30min.
[0097] 3.3 The nano-titanium dioxide-straw fiber obtained in step 3.2 was placed in an ultrasonic cleaning machine for cleaning, the cleaning time t3 was 8 minutes, the ultrasonic cleaning temperature was room temperature, and the ultrasonic cleaning medium was distilled water. Then it was dried in a drying oven, the drying temperature T1 was 112°C, and the drying time t4 was 150 minutes, and finally a nano-titanium dioxide-straw fiber multi-scale reinforcement was obtained.
[0098] The preparation method of copper-free NAO brake pads for high-end agricultural machinery and equipment, the specific steps are as follows:
[0099] 4.1 The granulated material for friction material described in the preparation of the copper-free NAO type brake pad for high-end agricultural machinery equipment comprises the following steps:
[0100] 4.1.1 Rubber powder, nitrile rubber modified phenolic resin, barite, shale, alumina, vermiculite powder, tire powder, purple sand, friction powder, potassium titanate platelets and copper powder substitute materials are placed in a three-dimensional motion mixer and mixed thoroughly. The mixing time t5 is: 3min;
[0101] 4.1.2 The mixed raw materials obtained in step 3.1.1 and the nano-titanium dioxide-straw fiber multi-scale reinforcement are placed in a paddle mixer and mixed thoroughly. The mixing time t6 is: 1 min;
[0102] 4.1.3 The mixed raw materials obtained in step 4.1.2 are placed in a granulator for granulation treatment, and the bridging liquid is continuously sprayed into the granulation drum. The rotation speeds of the granulation drum and the rotary cutter and the spraying amount of the bridging liquid are continuously adjusted. After sufficient granulation, a granulated material is obtained. The rotation speed r1 of the granulation drum is 20 r / min; the rotation speed r2 of the rotary cutter is 70 r / min, and the bridging liquid is a 3wt% corn starch paste solution.
[0103] 4.1.4 The granules obtained in step 4.1.3 are placed in a drying oven for drying to obtain the final granules. The drying temperature T2 is 100°C and the drying time t7 is 100 min. The granules obtained are cell-like in shape and have a diameter D3 of 1 mm.
[0104] 4.2 The mixing process in the preparation of brake pads includes the following steps:
[0105] 4.2.1 The nitrile rubber modified phenolic resin and the non-straw fiber are placed in a paddle mixer and mixed thoroughly. The mixing time t8 is 20 min.
[0106] 4.2.2 The mixture obtained in step 4.2.1 and the granulated material obtained in step 4.1.4 are placed in a three-dimensional motion mixer and mixed thoroughly. The mixing time t9 is 5 min to obtain the final mixed material for preparing the brake pad.
[0107] 4.3 Mold filling - hot pressing heat treatment - surface ablation - post-processing molding, including the following steps:
[0108] 4.3.1 Place the mixture obtained in step 4.2.2 into a special mold for brake pads for agricultural machinery and equipment, then perform hot pressing, and finally perform heat treatment and cool to room temperature;
[0109] 4.3.2 ablating the surface of the brake pad sample obtained in step 4.3.1 in a through-type ablation machine and cooling to room temperature;
[0110] 4.3.3 The ablated surface of the brake pad sample obtained in step 4.3.2 is surface polished, then ground and cut, then sprayed and baked, and finally a warning device or a retainer is installed to finally obtain a copper-free NAO type brake pad for high-end agricultural machinery equipment.
[0111] The friction coefficient of the friction material produced by the process of the above embodiment is in the range of 0.339 to 0.406, and the wear rate is 0.15 × 10 -7 cm 3 / Nm~0.26×10 -7 cm 3 / Nm, brake noise and brake dust are significantly reduced.
[0112] In the description of this specification, the description with reference to the terms "one embodiment", "some embodiments", "examples", "specific examples", or "some examples" means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described may be combined in any one or more embodiments or examples in a suitable manner.
[0113] Although the embodiments of the present invention have been shown and described above, it is to be understood that the above embodiments are exemplary and are not to be construed as limitations on the present invention. A person skilled in the art may change, modify, substitute and modify the above embodiments within the scope of the present invention without departing from the principles and purpose of the present invention.
Claims
1. A copper-free NAO type brake pad for high-end agricultural machinery and equipment, characterized in that: The content of each component by mass fraction is: 80-95% of granulated material for friction material, 0-10% of nitrile rubber modified phenolic resin and 2-15% of non-straw fiber; wherein the non-straw fiber includes one of rock wool fiber, sepiolite fiber or composite mineral fiber; The mass fraction of each component of the granulated material is as follows: 5-20% of nano-titanium dioxide-straw fiber multi-scale reinforcement, 1-5% of rubber powder, 5-20% of nitrile rubber modified phenolic resin, 5-21% of barite, 2-10% of shale, 5-24% of alumina, 1-3% of vermiculite powder, 1-5% of tire powder, 1-5% of purple sand, 1-5% of friction powder, 3-15% of potassium titanate platelets and 2-15% of copper powder substitute material; The copper powder substitute material is composed of 20-40% by mass of stainless steel grinding chips and 60-80% by mass of natural graphite; The preparation method of the nano titanium dioxide-straw fiber multi-scale reinforcement comprises the following steps: Step 1: The collected straw skin is crushed in a crusher, and then the crushed straw fiber is screened. The crushing time t1 of the straw skin is: 3min≤t1≤6min; the straw fiber length L1 is: 1mm≤L1≤3mm, and the fiber diameter D1 is: 0.01mm≤D1≤0.5mm; Step 2: Soaking the straw fiber obtained in step 1 in a grafting treatment device containing a suspension formed by nano-titanium dioxide and a silane solution to obtain nano-titanium dioxide-straw fiber, wherein the silane solution is composed of anhydrous ethanol, a silane coupling agent and distilled water, the mass ratio of each component is: 35-75:6-15:10-50, the particle size of the nano-titanium dioxide is D2: 2nm≤D2≤100nm, the mass fraction w1 of the nano-titanium dioxide in the suspension is: 0.5%≤w1≤25%, and the soaking time t2 of the straw fiber in the suspension is: 10min≤t2≤50min; Step three: Put the nano-titanium dioxide-straw fiber obtained in step two into an ultrasonic cleaning machine for cleaning, and then dry it in a drying box to finally obtain a nano-titanium dioxide-straw fiber multi-scale reinforcement. The ultrasonic cleaning time t3 is: 2min≤t3≤10min; the ultrasonic cleaning temperature is room temperature; the ultrasonic cleaning medium is distilled water; the drying temperature T1 is: 90℃≤T1≤112℃, and the drying time t4 is: 60min≤t4≤180min.
2. The copper-free NAO type brake pad for high-end agricultural machinery and equipment according to claim 1 is characterized in that: The nano titanium dioxide-straw fiber multi-scale reinforcement is composed of 20-70% by mass of corn straw fibers and 30-80% by mass of rice straw fibers.
3. The method for preparing the copper-free NAO type brake pad according to claim 1, characterized in that: The steps include: Including the preparation of granules for friction materials; Mixing during the preparation of brake pads; Mold filling - hot pressing and heat treatment - surface ablation - post-processing and molding.
4. The method for preparing the copper-free NAO type brake pad according to claim 3, characterized in that: The preparation of granules for friction materials includes: S1: Rubber powder, nitrile rubber modified phenolic resin, barite, shale, alumina, vermiculite powder, tire powder, purple sand, friction powder, potassium titanate platelets and copper powder substitute material are placed in a three-dimensional motion mixer and fully mixed. The mixing time t5 is: 3min≤t5≤8min; S2: putting the mixed raw materials obtained in step S1 and the nano-titanium dioxide-straw fiber multi-scale reinforcement into a paddle mixer and mixing them thoroughly, and the mixing time t6 is: 1min≤t6≤3min; S3: putting the mixed raw materials obtained in step S2 into a granulator for granulation treatment, spraying a bridging liquid into the granulation drum, adjusting the rotation speeds of the granulation drum and the rotary cutter and the spraying amount of the bridging liquid, and obtaining granules after sufficient granulation; the rotation speed r1 of the granulation drum is: 20r / min≤r1≤350r / min; the rotation speed r2 of the rotary cutter is: 70r / min≤r1≤90r / min, and the bridging liquid is one of distilled water, anhydrous ethanol and a corn starch paste solution with a mass fraction of 3wt%; S4: The granules obtained in step S3 are placed in a drying box for drying to obtain the final granules for friction material. The drying temperature T2 is: 100°C ≤ T2 ≤ 130°C, the drying time t7 is: 100min ≤ t7 ≤ 240min, and the obtained granules are cell-like in shape, with a diameter D3 of: 1mm ≤ D3 ≤ 8mm.
5. The method for preparing the copper-free NAO type brake pad according to claim 3, characterized in that: The mixing process in the brake pad preparation process includes the following steps: S1: putting the nitrile rubber modified phenolic resin and the non-straw fiber into a paddle mixer and mixing them thoroughly, and the mixing time t8 is: 5min≤t8≤20min; S2: The mixture obtained in step S1 and the granulated material for friction material are placed in a three-dimensional motion mixer for thorough mixing. The mixing time t9 is: 5min≤t9≤10min, to obtain the final mixed material for preparing the brake pad.
6. The method for preparing the copper-free NAO type brake pad according to claim 3, characterized in that: Mold filling - hot pressing heat treatment - surface ablation - post-processing molding, including the following steps: S1: placing the mixed material for preparing the brake pad into a special mold for preparing the brake pad, then performing a hot pressing treatment, and finally performing a heat treatment, and cooling to room temperature; S2: ablating the surface of the brake pad sample obtained in step S1 in a through-type ablation machine and cooling to room temperature; S3: The ablated surface of the brake pad sample obtained in step S2 is polished, then ground and cut, then spray-painted and baked, and finally a warning device or a fixing device is installed to finally obtain a copper-free NAO type brake pad.
Citation Information
Patent Citations
Ceramic particle composite resin-based anti-thermal-fading friction material and its preparation method
CN106928649B
A kind of rear disc brake material of truck and preparation method thereof
CN107061571B
A friction material, an organocarbon ceramic brake pad for a wear-resistant coated brake disc prepared therefrom, its preparation method, and its application.
CN109555802B
A halogenated braking material, its preparation method and application
CN110778629B
Passenger car friction material suitable for high speed of 200 kilometers and high deceleration speed of 0.8 G and preparation method of passenger car friction material
CN112855812A